Structural Challenges of Monetary Policy-Making in Iranian Economy and Comprehensive Processing Model of Policy-Making - Farhad Matinnafs; Fattah Sharifzadeh; Mahnaz Rabiee; Seyyed Ahmad Hosseini Gol Afshani (فصلنامه پژوهش‌های اقتصادی ایران, 2020)
Economic policies include policy-making in monetary- banking, financial and commercial aspects. Monetary policies are more important in bank-oriented economies and in this countries, The Government determines other policies based on monetary market policy. The present research is conducted concerningthe challenges of the national economy including inflation growth, price shocks, liquidity growth, bankruptcy of financial institutions and failed projects, with the goal of proposing a model for monetary policy-making process. In this research, an analytical model was designed based on a six-stage policy-making process, and effective organizations and factors were identified after explorative studies and interview with scholars. The Results confirmed the necessity of the existence of 8, 8, 12, 7, 7 , 11 organizations in the stages of identification, formulation, approval, implementation, evaluation and modification/ termination of policies, as well as confirmed the effect of 7 internal and 6 external factors on policy-making process.